2015
DOI: 10.1016/j.ridd.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in people with intellectual disabilities: A systematic review of the literature

Abstract: Further research in this field is required, notably prevalence studies which control for participant demographics and personal situations to obtain more accurate diabetes prevalence rates in this population group. People with ID and diabetes should be encouraged to participate in future research and we recommend exploring the feasibility of adapting current mainstream diabetes management programmes for these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 39 publications
3
71
2
1
Order By: Relevance
“…None feel fully prepared with sufficient knowledge, resources, accessible information and time to enable person‐centred care that adequately meets care needs and addresses the challenges presented to services (Taggart et al , ). The findings from this study supports the need to focus specifically on people with ID and diabetes, necessary given the growing evidence of their increasing longevity and multimorbidities and high prevalence of diabetes across the lifespan (McCarron et al ; McVilly et al ; Cooper et al ; MacRae et al ).…”
Section: Discussionsupporting
confidence: 76%
“…None feel fully prepared with sufficient knowledge, resources, accessible information and time to enable person‐centred care that adequately meets care needs and addresses the challenges presented to services (Taggart et al , ). The findings from this study supports the need to focus specifically on people with ID and diabetes, necessary given the growing evidence of their increasing longevity and multimorbidities and high prevalence of diabetes across the lifespan (McCarron et al ; McVilly et al ; Cooper et al ; MacRae et al ).…”
Section: Discussionsupporting
confidence: 76%
“…The reviews found mean prevalences of 8.7% 75 and 8.3% 76 for combined gestational, type 1 diabetes mellitus and T2DM, respectively, but the reviews were unable to report on specific types of diabetes. The overall prevalence of CVD among people with ID is unclear.…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 96%
“…Two recent reviews 75,76 have focused on diabetes prevalence among people with ID. The reviews were unable to distinguish between T2DM and other types of diabetes.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the fourth criterion has been considered not feasible when assessing some pre-clinical studies. 50 …”
Section: Quality Assessmentmentioning
confidence: 99%